Desenvolvimento sustentável na educação superior (DSES): a contribuição da pesquisa acadêmica - Danesi, Luiz Carlos (Universidade do Vale do Rio dos Sinos, 2018)
The present study aims at the defense of Thesis regarding the use of academic research in the Sustainable Development in Higher Education (SDHE), as a requirement to obtain a Doctorate in the Postgraduate Program in Production Engineering and Systems of the Polytechnic School of the University of Valley of the Sinos River - UNISINOS. The subject of the study addresses the SDHE. It questions the current contribution of the academic research in relation to the theme and its main objective is to propose contributions that increase the practices of the SDHE through the Teaching of Sustainability (TS). To this end, it investigated 4 non-state universities, evaluating 12 research projects and their contributions to the SDHE and TS practices. The organization of this work consists of the introduction; theoretical reference; methodology; analysis and discussion of results and bibliography. The Systematic Review of Literature (SRL) pointed to the gap in scientific production regarding the expansion of knowledge in the SDHE through the use of academic research results in TS. The revised literature was codified as SDHE, TS, Barriers to SDHE and Academic Research. Regarding the research methodology, it is a question of a research of inductive characteristic, as far as the scientific method is concerned, and an exploratory, multiple-case, qualitative study is evidenced. The research protocol presented the questions that were elaborated by the doctoral student, considering the SRL that guided a semi-structured process of data collection. The interviews with the researchers of the participating universities of the study were presential and through Skype. A System model in the SDHE to be used in the analysis and discussion of the results is also presented: we work with the synthesis of the findings: the dialogue with literature; the contributions of the Thesis; the final considerations pointing to the proof of the Thesis; the attendance to the objectives and the possibilities of future studies.
Keywords: Desenvolvimento sustentável; Educação superior; Pesquisa acadêmica; Sustainable development; Higher education; Academic research; ACCNPQ::Engenharias::Engenharia de Produção